Treatment of Methicillin-Resistant Staphylococcus aureus: Vancomycin and Beyond - Holmes, Natasha E.; Tong, Steven Y. C.; Davis, Joshua S.; van Hal, Sebastiaan J. (Seminars in Respiratory and Critical Care Medicine, 2015)
There has been a welcome increase in the number of agents available for the treatment of methicillin-resistant Staphylococcus aureus (MRSA). Vancomycin remains an acceptable treatment option, with moves toward individualized dosing to a pharmacokinetic/pharmacodynamic (PK/PD) target. Numerous practicalities, however, would need to be resolved before implementation. Lipoglycopeptides as a class show excellent in vitro potency. Their long half-lives and complex PKs may preclude these agents being used in critically ill patients. Anti-MRSA cephalosporins provide great promise in the treatment of MRSA. These agents, despite broad-spectrum activity, should be reserved for patients with MRSA infections as it is likely that usage will be associated with increased rates of resistance. Daptomycin is currently the only antibiotic to have shown noninferiority to vancomycin in the treatment of MRSA bacteremia. The results of an open-labeled trial to address the superiority of daptomycin compared with vancomycin in reduced vancomycin susceptibility infections are eagerly anticipated. No drug to date has shown superiority to vancomycin in the treatment of MRSA infections with the possible exception of linezolid in hospital-acquired pneumonia (HAP), making linezolid an important option in the treatment of MRSA-proven HAP. Whether these strengths and features are agent or class specific are unclear but will likely be answered with the marketing of tedizolid. There are insufficient data to recommend either quinupristin/dalfopristin or tigecycline, as first line in the treatment of severe MRSA infections. These agents however remain options in patients with no other alternatives.
Keywords: methicillin-resistant Staphylococcus aureus; vancomycin; individualized dosing; daptomycin; linezolid; lipoglycopeptides; β-lactams